SARS-CoV-2 Spike Protein Expression In Vitro and Hematologic Effects in Mice Vaccinated With AZD1222 (ChAdOx1 nCoV-19) - Stebbings, Richard; Jones, Christopher; Cotton, Peter; Armour, Gillian; Maguire, Shaun; Skellett, Vicky; Tang, Chi-Man; Goodman, Joanne; Brady, Tyler; Takahashi, Virginia; Daunt, Andrew; Lapointe, Jean-Martin; et al. (Frontiers in Immunology, 2022)
Severe COVID-19 can be associated with a prothrombotic state, increasing risk of morbidity and mortality. The SARS-CoV-2 spike glycoprotein is purported to directly promote platelet activation via the S1 subunit and is cleaved from host cells during infection. High plasma concentrations of S1 subunit are associated with disease progression and respiratory failure during severe COVID-19. There is limited evidence on whether COVID-19 vaccine-induced spike protein is similarly cleaved and on the immediate effects of vaccination on host immune responses or hematology parameters. We investigated vaccine-induced S1 subunit cleavage and effects on hematology parameters using AZD1222 (ChAdOx1 nCOV-19), a simian, replication-deficient adenovirus-vectored COVID-19 vaccine. We observed S1 subunit cleavage in vitro following AZD1222 transduction of HEK293x cells. S1 subunit cleavage also occurred in vivo and was detectable in sera 12 hours post intramuscular immunization (1x1010 viral particles) in CD-1 mice. Soluble S1 protein levels decreased within 3 days and were no longer detectable 7–14 days post immunization. Intravenous immunization (1x109 viral particles) produced higher soluble S1 protein levels with similar expression kinetics. Spike protein was undetectable by immunohistochemistry 14 days post intramuscular immunization. Intramuscular immunization resulted in transiently lower platelet (12 hours) and white blood cell (12–24 hours) counts relative to vehicle. Similarly, intravenous immunization resulted in lower platelet (24–72 hours) and white blood cell (12–24 hours) counts, and increased neutrophil (2 hours) counts. The responses observed with either route of immunization represent transient hematologic changes and correspond to expected innate immune responses to adenoviral infection.